Pengaruh ekstrak ikan patin pada aktivitas katalase dan kadar MDA serum tikus yang diinduksi aloksan - Handajani, Fitri; Nabil; Pranitasari, Nita (Jurnal Kedokteran Meditek, 2025)
Introduction: Pangasius fish is known to contain antioxidants. Catalase is an enzymatic antioxidant whose role is to reduce oxidative stress. Oxidative stress results in fat oxidation which can be checked by Malondialdehyde (MDA) levels. Alloxan induction will cause oxidative stress. Purpose: This study aims to decide the role of Pangasius extract on catalase and MDA activity in alloxan-induced experimental animals. 24 hundred Rattus norvegicus were isolated into K0 the group without treatment, K1 was the group induced by an intraperitoneal (i.p) alloxan dose of 150 mg/kgBB on the 7th day, K2 was the group that was induced by an alloxan dose of 150 mg/kgBB i.p on the 7th day and given Pangasius fish oil extricate dosage of 73 mg/kgBB on the 10th day intragastric every day to 14 days. Results: The data investigation showed that there were significant differences in pancreatic catalase activity between groups K0 and K1 (p=0.001) and between groups K1 and K2 (p=0.001). These conditions indicate that Pangasius extract can scavenge free radicals so that there is no decrease in catalase activity in the pancreas. Pancreatic MDA levels showed significant results between groups K0 and K1 (p=0.010) and between groups K1 and K2 (p=0.010). This is due to the ability of the antioxidants contained in Pangasius fish extract to reduce free radicals thereby reducing oxidative stress resulting in decreased lipid peroxidation. Conclusion: the administration of Pangasius extract 73 mg/kgBW can decrease free radicals formed due to alloxan induction so that it can increase catalase activity and reduce pancreatic MDA